The Elections of the Great Recession in Portugal: Performance Voting under a Blurred Responsibility for the Economy - Magalhães, Pedro (2014)
This article discusses the basic patterns of voting behaviour in the most recent elections in Portugal. These elections were fought under one of the most profound economic crises in the country's four decades of democracy, after a bailout agreement with the EU and the IMF, and under an unusually high level of campaign polarization around the issues of economic austerity and liberalization. First, the article examines whether this context ended up being favourable to “performance” voting or, instead, to an enhanced importance of position issues, particularly those related to the role of the state in the economy and welfare provision. Second, it examines how the context of the Great Recession and the European sovereign debt crisis created opportunities for incumbents to use blame-shifting and blame-sharing strategies, and the extent to which voters' ambivalence about who to hold responsible for the sorry state of the economy was consequential for vote choices, either by directly affecting them or by moderating the relationship between economic perceptions and the vote.